Rupture in long-term vocal recognition of past social partners in bonobos - Sumir Keenan; Nicolas Mathevon; Jeroen Stevens; Jean-Pascal Guéry; Klaus Zuberbühler; Florence Levréro (Revue de Primatologie)
Bonobos live in dense forest habitats where visual communication is often limited rendering vocal signals important to regulate their social interactions. Moreover their fluid fission-fusion society requires contact over long distances, suggesting that vocal signals of group members are recognised individually. To this end, individual signatures should be reliably encoded in vocal interactions and memorised by recipients over long periods. In this study we investigated individual vocal recognition of group members that had been separated for long periods of time (two to nine years) with varying relationships. In the wild, long-term separation happens regularly, usually in relation to female migration. In captivity, the same process takes place during the transfer of individuals between zoos, mimicking wild migration. We simulated bonobo transfers by broadcasting contact calls of familiar or unfamiliar individuals to our subjects, thus imitating the arrival of new group members. In total, we tested 15 bonobos (> 10 years old) from three European zoos and compared their behavioural responses. We found that bonobos responded differently to familiar voices than to stranger voices, even after prolonged separation. However, the recognition of past partners appears to diminish after being separated for 6-8 years. This interesting result will be discussed regarding to the social needs in bonobos.